USING OF POWERED PARAGLIDER IN THE TAUISKAYA GUBA BAY, THE OKHOTSK SEA, FOR LOCAL AIREAL SURVEYS AND OBSERVATIONS ON EARLESS SEALS - M. B. Gorshunov (Известия ТИНРО)
Powered paraglider using for local aerial surveys and observations on real seals is described in combination with routine watch from the coastal observation point and motor boat. The results of conventional and combined observations are compared.